Asymmetric Chiral Ligand-Directed Alkene Dioxygenation - Neufeldt, Sharon R. (2012)
[Image: see text] A Pd-catalyzed asymmetric alkene 1,2-dioxygenation reaction is described. The diastereoselectivity of the reaction is controlled by tethering a chiral oxime ether directing group to the alkene substrate. The best selectivities are obtained with 8-substituted menthone-derived oxime ether auxiliaries.